ARAH DAN IMPLEMENTASI KEBIJAKSANAAN PROGRAM KELUARGA BERENCANA DI INDONESIA* - Siswanto Agus Wilopo (Populasi, 1997)
There are some interesting differences between the Family Planning Program in Indonesia and the family planning in Cairo Action Program. The FP Program has larger actions, such as the society's attention to the increasing age limit of marriage, family resistance building, increasing the family welfare, and birth control. While, the family planningin Cairo Action Program is only limited to the birthcontrol. This writing tries to describe those differences as well as to clarify the direction and the implementation of the FP Program which increasingly become an FP movement.